A Systematic Literature Review of Smes Family Business, Digital Innovation, Business Sustainability based on Google Scholar Scientific Mapping - Ayuanti, Rafikhein Novia; Hermawan, Agus; Selviasari, Rike (Formosa Journal of Science and Technology, 2024)
This review aims to conduct a systematic literature review of Small and Medium Enterprises (SMeS) family businesses, digital innovation, and business sustainability. Using Google Scholar scientific mapping. This research aims to analyze a systematic literature review of international scientific articles on the theme of MSME entrepreneurial orientation. This research focuses on the perspective of data search using keywords, research location, research subjects, and research methods used. Using a systematic search method, relevant research articles will be identified and analyzed based on their methodological quality and relevance to the research theme. It is hoped that the findings from this review will make a significant contribution to the understanding of family businesses. Ultimately, the insights gained can be used to develop more effective policies and programs to support the success of family-owned MSMEs, digital innovation, business sustainability.